Problematika Haji dan Umrah Berulang Kali Menurut Ali Mustafa Yaqub dalam Perspektif Fikih Islam: The Problems of Repeated Hajj and Umrah According to Ali Mustafa Yaqub in the Perspective of Islamic Jurisprudence - Muhammad, Muhammad; Muammar Bakry; Andi Muhammad Akmal (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to discuss the problems of repeated Hajj and Umrah according to Ali Mustafa Yaqub from the perspective of Islamic jurisprudence. This research includes library research with a normative and methodological approach. The existing data was collected then processed and analyzed using content analysis and comparative analysis methods. The results of the research show that Ali Mustafa Yaqub's opinion in forbidding or disallowing Hajj and Umrah is repeatedly different from what is understood by fiqh scholars. The Prophet's deeds. who only performs Hajj once and performs Umrah four times not because he hates this act, but because of several other reasons behind it. The argument that social worship is more important than the Sunnah Hajj and Umrah is also inappropriate because it is only based on a textual understanding of the propositions. Every Muslim may perform the Hajj or Umrah whenever he is able to do it while taking into account the advantages and disadvantages that may occur during the journey, such as when he does not have the physical strength or funds, the atmosphere is not conducive, or for other reasons that cause someone not to be able to go at that time.